(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Tax fraud is following different methods of tax evasion (bypassing the laws, instructions and regulations related to tax) by not showing the real taxable income by using laws, instructions and regulations improperly, and because of the weak basic role of forensic accounting in detecting and reducing tax fraud, the problem has become more influential on the state general tax income. The main objective of the research is to identify forensic accounting and the extent to how it can be applied in the General Tax Authority to assist forensic authorities in issuing judgments in fraud cases. To achieve the objectives of the research, the descriptive analytical approach was used to reach the topic of the research, and a questionnaire (consist of 24 items) was evaluated as a tool for data collection. In order to test the research hypotheses, a set of statistical measurements were used to analyze the data and reach the results using the SPSS statistical application.